A Randomized Controlled Trial of the Effect of Early Upper-Limb Training on Stroke Recovery and Brain Activation. (September 2015) - Hubbard, Isobel J.; Carey, Leeanne M.; Budd, Timothy W.; Levi, Christopher; McElduff, Patrick; Hudson, Steven; Bateman, Grant; Parsons, Mark W.
Background . Upper-limb (UL) dysfunction is experienced by up to 75% of patients poststroke. The greatest potential for functional improvement is in the first month. Following reperfusion, evidence indicates that neuroplasticity is the mechanism that supports this recovery. Objective . This preliminary study hypothesized increased activation of putative motor areas in those receiving intensive, task-specific UL training in the first month poststroke compared with those receiving standard care. Methods . This was a single-blinded, longitudinal, randomized controlled trial in adult patients with an acute, first-ever ischemic stroke; 23 participants were randomized to standard care (n = 12) or an additional 30 hours of task-specific UL training in the first month poststroke beginning week 1. Patients were assessed at 1 week, 1 month, and 3 months poststroke. The primary outcome was change in brain activation as measured by functional magnetic resonance imaging. Results . When compared with the standard-care group, the intensive-training group had increased brain activation in the anterior cingulate and ipsilesional supplementary motor areas and a greater reduction in the extent of activation ( P = .02) in the contralesional cerebellum. Intensive training was associated with a smaller deviation from mean recovery at 1 month (Pr>F0 = 0.017) and 3 months (Pr>F = 0.006), indicating more consistent and predictable improvement in motor outcomes. Conclusion . Early, more-intensive, UL training was associated with greater changes in activation in putative motor (supplementary motor area and cerebellum) and attention (anterior cingulate) regions, providing support for the role of these regions and functions in early recovery poststroke.